Somatovisceral Influences on Emotional Development. (April 2023) - Faig, Kelly E.; Smith, Karen E.; Dimitroff, Stephanie J.
Frameworks of emotional development have tended to focus on how environmental factors shape children's emotion understanding. However, individual experiences of emotion represent a complex interplay between both external environmental inputs and internal somatovisceral signaling. Here, we discuss the importance of afferent signals and coordination between central and peripheral mechanisms in affective response processing. We propose that incorporating somatovisceral theories of emotions into frameworks of emotional development can inform how children understand emotions in themselves and others. We highlight promising directions for future research on emotional development incorporating this perspective, namely afferent cardiac processing and interoception, immune activation, physiological synchrony, and social touch.